Congenital Infection of Severe Acute Respiratory Syndrome Coronavirus 2 With Intrauterine Fetal Death: A Clinicopathological Study With Molecular Analysis. (23rd September 2021) - Lesieur, Emmanuelle; Torrents, Julia; Fina, Frédéric; Zandotti, Christine; Blanc, Julie; Collardeau-Frachon, Sophie; Gazin, Céline; Sirgant, Delphine; Mezouar, Soraya; Otmani Idrissi, Myriem; Lepidi, Hubert; Bretelle, Florence; et al.
Abstract: Background: Observations of vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection from mother to fetus have recently been described in the literature. However, the consequences of such transmission, whether fetal or neonatal, are poorly understood. Methods: From a case of in utero fetal death at 24 +2 weeks of gestation that occurred 7 days after the diagnosis of symptomatic SARS-CoV-2 infection in the mother, we isolated the incriminating virus by immunochemistry and molecular techniques in several fetal tissues, with a variant analysis of the SARS-CoV-2 genome. Results: The fetal demise could be explained by the presence of placental histological lesions, such as histiocytic intervillositis and trophoblastic necrosis, in addition to fetal tissue damage. We observed mild fetal growth retardation and visceral damage to the liver, causing hepatocellular damage and hemosiderosis. To the best of our knowledge, this is the first report in the literature of fetal demise secondary to maternal–fetal transmission of SARSCoV- 2 with a congenital infection and a pathological description of placental and fetal tissue damage. Conclusions: SARS-CoV-2 was identified in both specimens using 3 independent techniques (immunochemistry, real-time quantitative polymerase chain reaction, and realtime digital polymerase chain reaction). Furthermore, the incriminating variant has been identified. Abstract : From a case of in utero fetal death that occurred after the diagnosis of symptomatic SARSCoV-2 infection in the mother, we isolated the incriminating virus in several fetal tissues, with a variant analysis of the SARS-CoV-2 genome.